Whale entanglements in South African trap fisheries and their potential mitigation through ropeless fishing techniques - Daniel, Michael Talbot (Department of Biological Sciences, 2023)
The increasing frequency of whale entanglements in fishing gear is a global concern. In South African waters, the west coast rock lobster (WCRL), south coast rock lobster (SCRL) and octopus fisheries are responsible for whale entanglements in trap fishing gear. To better understand the interactions between whale species and fishing gear, a study was conducted in which whale entanglement and fishing effort data were analysed. Annual whale entanglements increased since 2006, despite an overall decrease in trap fishing effort. Entanglement hotspots corresponded with fishing hotspots. The WCRL fishery was responsible for 68% of all entanglements between 2006 and 2020. Of particular concern was zone D of the WCRL fishing area, where 90% of whale entanglements in the fishery occurred; the same area where 92% of fishing effort took place. Entanglements in SCRL fishing hotspot, near the remote southern tip of the Agulhas Bank, are likely to be underreported. Humpback (Megaptera novaeangliae), southern right (Eubalaena australis) and Bryde's (Balaenoptera brydei) whales accounted for 64%, 25%, and 11% of entanglements, respectively. Species and area specific GLMs showed that humpback whale entanglements increased over the whole South African coastline and in all trap fisheries. This increase was attributed to the aggregation of humpback whales in ‘super-groups' off the west coast during summer months over the past decade. Consequently, a primary seasonal peak in entanglements occurred between January and March. Southern right whale entanglements decreased since 2006 over the whole South African coastline and in the WCRL fishery. This decrease was attributed to a northern shift in foraging by this species over the past decade. Bryde's whale entanglements increased since 2006 across the South African coastline, and most strongly in the octopus fishery. Since all Bryde's entanglements occurred in the past six years, a change in distribution of the species is suspected. Bryde's whale entanglements are of high concern due to their small resident population. The octopus fishery posed the greatest threat to Bryde's whales, and the WCRL fishery the least. Along with the analyses of whale entanglements, the feasibility of ropeless fishing techniques was analysed for use in South African trap fisheries. This analysis included the testing of sinking line as ground line to reduce rope arcs between traps, the testing of three ropeless fishing release mechanisms and two rope storage systems. The results of the ground line rope tests confirmed that the use of floating rope will produce arcs between traps of sufficient height to pose threats to whales. Sinking line was effective in eliminating arcs between traps. Concerns that burial of sinking line to the extent that grappling and retrieval are affected were unfounded. Three types of releases were tested for use in ropeless fishing techniques, namely galvanic timed releases (GTRs), an electronic timed release (ETR), and an acoustic release. The electronic timed release (ETR), acoustic release, the bag rope storage system and the pipe rope storage system all demonstrated at least 85% reliability. The importance of ensuring the release is set up correctly before deployment was crucial to ensuring a successful release. The variation in release times of GTRs of the same size confirmed that their release time ranges were sufficient to reduce buoy line time in the water column by 84%. This reduction in buoy line time would reduce the probability of it entangling a whale by the same percentage. Profit estimates in the WCRL fishery suggest that locally manufactured GTRs would be a feasible option in the fishery. The simplicity of the GTR systems could also provide an opportunity for stakeholders to familiarise themselves with ropeless fishing techniques, enabling the development of systems to better suit their needs, before moving to acoustic systems if necessary. Although the SCRL fishery can afford acoustic ropeless fishing systems, a similar approach may be beneficial to avoid costly mishaps while trialling expensive acoustic systems. GTRs and electronic timed release were determined as undesirable by the octopus fisherman due to the uncertainty of retrieval times which are based on weather conditions. Octopus fishers have subsequently started trialling 10 acoustic release ropeless fishing systems in False Bay. These trials, which implement the bag rope storage systems developed in this study, have shown that time is necessary for fishermen to familiarise themselves with these systems, with efficiencies improving with practise. These trials also showed that these systems withstand the rigors of commercial conditions. If the replacement of existing gear with ropeless fishing systems is done in stages, then cost can be spread over multiple years. A similar staged approach could be implemented in the WCRL fishery with the use of spatial management, where ropeless fishing systems are made a requirement when fishing in entanglement hotspots. The ‘user pays' principle was suggested as a potential management strategy to incentivise fisherman to reduce whale entanglements in the WCRL, SCRL and octopus fisheries. This would be done by making fisherman liable for the costs associated with whale entanglements. However, in order to be effective, sufficient individual gear identifiers would be crucial to accurately assign liability. Therefore, a better option may be for the fishing authority to alter the rules of fishing to ensure that ropeless fishing techniques (of one form or another) become mandatory and that every reasonable step be taken to reduce the risk of entanglement. Whichever management approach or policy changes are decided upon, if stakeholders were involved in the research and development process, it is more likely that they will buy into an improved and more sustainable fishing method.